A Longitudinal Study of Foreign Language Enjoyment and L2 Grit: A Latent Growth Curve Modeling - Elahi Shirvan, Majid; Taherian, Tahereh; Shahnama, Mojdeh; Yazdanmehr, Elham (Frontiers in Psychology, 2021)
In line with the dynamic shift in SLA domain and the need for the development of suitable methods to explore the dynamics of emerging concepts in the field such as grit and enjoyment, in the present research, we intended to investigate the growth of foreign language enjoyment (FLE) and L2 grit over time. To do this, we used a bivariate latent growth curve model (LGCM) to examine the covariance between 437 EFL learners’ initial and growth levels of L2 grit and FLE in four measurement occasions of two week intervals. The data were collected via the original foreign language scale and the L2 grit scale. The model including the covariance between intercepts and slopes of FLE and L2 grit was tested via Mplus 7. The findings indicated an increasing trend in the association between the growth levels of both variables. That is, the means of both L2 grit and FLE were larger at their growth level than their initial level. Also, analyzing the co-variations in the model showed that the covariances between the intercepts and slopes of FLE and L2 grit were statistically significant. This would point to the existence of a parallel process (co-development) of FLE and L2 grit. This result also implied that an increase in the level of FLE among the participants was strongly correlated with an increase in the level of L2grit during the whole course. The findings were discussed with reference to previous studies in the literature and the implications were also provided.